Diet shifts and delayed piscivory specialisation during the ontogenesis of the largemouth bass Micropterus salmoides (Lacepede, 1802)Â in the Nakdong River and Upo Wetlands, South Korea - Jo, Hyunbin; Yoon, Ju-Duk; Kim, Jeong-Hui; Jeong, Kwang-Seuk; Do, Yuno; Joo, Gea-Jae (Indian Journal of Fisheries, 2016)
In this study, we examined the ontogenetic changes in prey selection pattern of largemouth bass Micropterus salmoides (Lacepede, 1802) in accordance with habitat type. The stomach contents of largemouth bass were analysed with respect to predator size classes for two different habitats (Nakdong River main channel and the Upo Wetlands tributary) in South Korea, that differed in the diversity of potential prey items. The diversity (H′) of invertebrate diet items in stomach of largemouth bass was found significantly different between the study sites. Small large mouth bass (100 mm in the river and >200 mm in the wet land system preferred fish as their prey. Results demonstrated variations in composition of prey items as influenced by habitat characteristics as well as habitat use type, contributed to the delayed ontogenetic diet shift in the largemouth bass population.